Christmas Eve at Friday Harbor - Kleypas, Lisa (Kleypas, Lisa. Friday Harbor novel., 2010)
Mark Nolan's happy-go-lucky bachelorhood is interrupted by the death of his sister and his subsequent guardianship of her six-year-old daughter, Holly, who is traumatized into muteness and desperately seeking a maternal figure. Enter Maggie Collins, a toy shop owner who lost her own husband to cancer.